Indications of ventriculoperitoneal shunt: a prospective study - Jaykar, Ritvik D.; Patil, Shrikant P. (International Surgery Journal, 2017)
Background: Shunts have been used to drain the Cerebrospinal fluid into practically every body cavity, organ system and tissue spaces. Scraff has critically reviewed the efficacy of various shunts. These are of historical interest. Ventriculo peritoneal and ventriculo cardiac shunts continue to remain the chief surgical techniques in the management of hydrocephalus. Methods: This study included sixty cases where VP shunt insertion surgery was indicated. Chhabra’s medium pressure VP shunt was used in all 60 cases. 32 out of 60 cases were below 2 years (53.3%) .70% of the patients were male and 30% were female. Male to female ratio was 2.3:1. Out of 24 cases of congenital hydrocephalus 16 were due to aqueductal stenosis i.e. 66.6 % of cases. Dandy Walker malformation was found in 2 cases. And in 2 more cases, Arnold Chiari malformation was found. In acquired group 22 cases had tuberculous meningitis, 4 cases were of post meningitis aetiology and 10 cases were of communicating hydrocephalus with history of trauma. Results: In congenital group of patients, most common clinical feature was ‘enlargement of head’ bulging of fontanelle. In acquired group of patients the common clinical features were headache, vomiting, fever and convulsions. USG cranium and CT scan proved to be highly informative investigations and were done wherever necessary. Out of 36 cases of acquired group the percentage of tuberculous meningitis was 61.6% and communicating hydrocephalus with trauma was about 27%. USG cranium was also used in follow up congenital hydrocephalus to assess the position and functioning of shunt. Even CT scan was used in adult age group to assess the position of shunt and condition of the brain. All patients of with VP shunt surgery were treated with higher antibiotics preoperatively and postoperatively. Conclusions: Common complications included, shunt infections, shunt obstruction, shunt malposition. Rare complications included shunt migration through anus and shunt ascites. Four patients died after VP shunt surgery, two were operated case of encephalocele with associated congenital anomalies with uremia and other two were with dreaded shunt infection with septicaemia. Ten (16.6%) patients required revision of VP shunt surgery in present study.